I've been everywhere (except Mexico): Investor responses to NAFTA's cross-border trucking provisions - Ronald B. Davies; Benjamin H. Liebman; Kasaundra Tomlin (University College Dublin, UCD School of Economics, 2015)
We investigate the response of US trucking firms to the removal of barriers to crossborder trucking under NAFTA. This was done via a program implemented in 2007, cancelled in 2009, and reinstated in 2011. We find that, unsurprisingly, the program's start resulted in lower stock returns, particularly for border firms. However, later policy changes indicate that investors, and particularly those in US multinationals, viewed the pilot as beneficial. We use a model of endogenous exporting to show that this can arise from incorrect expectations of import competition.
Keywords: F13; F15; F20; 330; Non-tariff Barriers; Services; Commercial Policy; Protection; Promotion; Trade Negotiations